2018
DOI: 10.1111/iej.12945
|View full text |Cite
|
Sign up to set email alerts
|

Longevity of bond strength of resin cements to root dentine after radiation therapy

Abstract: Radiation was associated with a decrease in the push-out bond strength and with lower resin cement/root dentine interface adaptation. Self-adhesive resin cement was a better alternative for fibre post cementation in teeth subjected to radiation therapy. The bond strength decreased after 6 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
29

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(69 citation statements)
references
References 44 publications
0
30
0
29
Order By: Relevance
“…Radiotherapy has a semi-selective character, and the surrounding tissues are not always preserved (Ro s-Mazurczyk et al 2017) causing side effects in the oral cavity, including radiation carious lesions (Lieshout & Bots 2014, Gupta et al 2015, Dobro s et al 2016, Qing et al 2016, which can cause severe tooth destruction, leading these patients to seek functional and aesthetic restorations. Recent studies have shown that in these cases, the longevity of adhesive restorations is compromised (Naves et al 2012, Rodrigues et al 2018, Yamin et al 2018, confirming the importance of establishing clinical protocols that provide satisfactory dental treatments, thus improving the patient's quality of life.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Radiotherapy has a semi-selective character, and the surrounding tissues are not always preserved (Ro s-Mazurczyk et al 2017) causing side effects in the oral cavity, including radiation carious lesions (Lieshout & Bots 2014, Gupta et al 2015, Dobro s et al 2016, Qing et al 2016, which can cause severe tooth destruction, leading these patients to seek functional and aesthetic restorations. Recent studies have shown that in these cases, the longevity of adhesive restorations is compromised (Naves et al 2012, Rodrigues et al 2018, Yamin et al 2018, confirming the importance of establishing clinical protocols that provide satisfactory dental treatments, thus improving the patient's quality of life.…”
Section: Discussionmentioning
confidence: 93%
“…Radiotherapy X‐rays act in the presence of water through the formation of free radicals and hydrogen peroxide (Cole & Silver , Fisher et al ), capable of acting as a strong oxidant, causing the denaturation and fragmentation of the dentine collagen fibres network (Pioch et al , Aggarwal , Kochueva et al , Gonçalves et al , Qing et al ), besides activating metalloproteinases (Strup‐Perrot et al , Mcguire et al ). Thus, the degradation of the collagen fibre network is probably related to the lower bond strength values of the resin cement to root dentine observed in the irradiated teeth (Aggarwal , Rodrigues et al , Yamin et al ), as well as in the greater mismatch of the adhesive interface observed in SEM (Figs and ) (Gonçalves et al , Lieshout & Bots ), since the RelyX U200 resin cement bonding mechanism is promoted by acid monomers that, when interacting with the organic part of the resin cement and with the root dentine, demineralize and penetrate the dentine, creating micromechanical retention and chemical bonding to the hydroxyapatite. It does not depend on hybrid layer formation or presence of tags (Ferracane et al ), but rather of an ionization medium for the chemical reaction to occur (Mushashe et al ), which when altered by irradiation may have led to a lower number of chemical bonds between the cement and root dentine (Yamin et al ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations